2019
DOI: 10.3390/app9061049
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanomaterials for Energy Applications: Recent Advances

Abstract: Electrospinning is a simple, versatile, cost-effective, and scalable technique for the growth of highly porous nanofibers. These nanostructures, featured by high aspect ratio, may exhibit a large variety of different sizes, morphologies, composition, and physicochemical properties. By proper post-spinning heat treatment(s), self-standing fibrous mats can also be produced. Large surface area and high porosity make electrospun nanomaterials (both fibers and three-dimensional fiber networks) particularly suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 262 publications
(511 reference statements)
0
34
0
1
Order By: Relevance
“…It has been shown that electrospinning is an appropriate method for embedding oxygen reductive materials into porous carbon-based fibers. Additionally, mesoporous structure of electrospun nanofibers provides facile gas diffused channels for increasing oxygen–electrolyte interface [ 20 , 112 ]. According to Tsou et al, electrochemical performance of oxygen electrode catalyst in Li-O 2 batteries was improved by combining the bifunctional catalytic property of active catalyst with interconnected structural features of carbon nanofibers using iron phthalocyanine as the bifunctional catalyst covalently bonded to pyridine-functionalized electrospun N-doped carbon nanofibers as the carbon supports [ 113 ].…”
Section: Energy Storagementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that electrospinning is an appropriate method for embedding oxygen reductive materials into porous carbon-based fibers. Additionally, mesoporous structure of electrospun nanofibers provides facile gas diffused channels for increasing oxygen–electrolyte interface [ 20 , 112 ]. According to Tsou et al, electrochemical performance of oxygen electrode catalyst in Li-O 2 batteries was improved by combining the bifunctional catalytic property of active catalyst with interconnected structural features of carbon nanofibers using iron phthalocyanine as the bifunctional catalyst covalently bonded to pyridine-functionalized electrospun N-doped carbon nanofibers as the carbon supports [ 113 ].…”
Section: Energy Storagementioning
confidence: 99%
“…Electrospinning offers opportunities for designing and manufacturing new materials for improving the energy generation, conversion, and storage devices. Application of electrospun nanofibrous materials for energy and environmental issues have been studied in several reviews [ 17 , 18 , 19 , 20 ]. Still, with the rising demand on energy resources and environmental remediation, an updated and systematic review is a necessity to identify the future directions of the field.…”
Section: Introductionmentioning
confidence: 99%
“…There have been two types of typical review articles on the electrospun nanofiber anode materials: (i) focusing on specific materials and structures (e.g., reviews of carbon, silicon, tin, and their composite nanofibers and nanostructures for lithium rechargeable batteries [ 20 , 21 , 22 , 23 , 24 ] and hollow, porous, and hierarchical structured nanofibers for energy applications [ 25 , 26 , 27 ]) and (ii) providing a broad overview of recent research and developments [ 28 , 29 , 30 , 31 ]. Regardless of the review types, the electrospun nanofiber anode materials in the previous review articles were mostly categorized into the material classes, for example, carbon, metals, and metal oxides, and so on [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning has attracted considerable attention as a simple and efficient alternative method to produce LIB separators with a nanoporous structure and high porosity. [19][20][21] This special structure allows the liquid electrolyte to be easily encapsulated in the matrix, which contributes to a good ion-conduction channel and the high ionic conductivity of the separator. [16,22,23] However, the large pore size of electrospun separator can yield self-discharge, an uneven current distribution, and safety concerns when these nanofibers are directly used as the separator of the LIBs.…”
Section: Introductionmentioning
confidence: 99%